The relationship between frequency of change, planning involved in change and magnitude of change among young professional perception towards job satisfaction at Pertubuhan Peladang Kawasan Parit Raja / Nur Fatin Nadzirah Zaman - Zaman, Nur Fatin Nadzirah (Faculty of Business and Management, 2018)
This research been conducted to focus more on relationship change variable towards job satisfaction. Job satisfaction study is evergreen study due to almost of organization want to have good-term relationship towards their employees and identified factors make them satisfied in the workplace. Besides, having a good term relationship. It can help organization to generate e a good image and increases employee’s perception towards organization. Therefore, this organization focus on what young professional employees perceived about three change perceptions towards job satisfaction when changes happen. This research has been carrying out at Pertubuhan Peladang Kawasan Parit Raja. Moreover, the organization is government linked company, it shown that certain variable may not have significant towards dependent of this study. The research is a quantitative research and the questionnaire been hand out to respondent by the researcher itself due to this study focus on young professional employees and have tertiary level of education. Total sample size for this study is 30 employees out of 42 employees. The sample selection was based on simple random method. The data collected been formulated by SPSS Software version 20. Using this software, various of analysis be run to get the numerical data and interpret by various analysis. The result indicated change perception such as frequency of change and magnitude of change of changes has related relationship towards job satisfaction, but planning involved shown have relationship but not significant towards job satisfaction.